Pre/post-natal exposure to microplastic as a potential risk factor for autism spectrum disorder. (March 2022) - Zaheer, Javeria; Kim, Hyeongi; Ko, In Ok; Jo, Eun-Kyeong; Choi, Eui-Ju; Lee, Hae-June; Shim, Insop; Woo, Hyun-jeong; Choi, Jonghoon; Kim, Gun-Ha; Kim, Jin Su
Graphical abstract: Highlight: Prenatal exposure to Polyethylene (PE) lead to Autism spectrum disorder (ASD) like traits in mice. Exposure to PE leads to impaired social interaction and repetitive behaviors in mice model. Exposure to PE leads to disturbance of metabolites and gene expression in brain. Exposure to PE leads gut microbiome change revealed ASD like traits in mice. Our finding on ASD in prenatal model was well supported based on already revealed findings. Abstract: In common with the increase in environmental pollution in the past 10 years, there has also been a recent increase in the prevalence of autism spectrum disorder (ASD). In this regard, we hypothesized that exposure to microplastics is a potential risk factor for ASD. To evaluate the validity of this hypothesis, we initially examined the accumulation of polyethylene (PE) in the brains of mice and then assessed the behavioral effects using mouse models at different life stages, namely, prenatal, post-weaning, puberty, and adult models. Based on typical behavioral assessments of autistic traits in the model mice, we established that ASD-like traits were induced in mice after PE feeding. In addition, we examined the induction of ASD-like traits in response to microplastic exposure using positron emission tomography, magnetic resonance spectroscopy, quantitative real-time polymerase chain reaction, microarray, and microbiome analysis. We believe these findings provide evidence in microplastics as a potential risk factor for ASD.